Composite hydrogen storage material as well as preparation method and application thereof

By mixing aluminum hydride powder with lanthanum nitride particles and ball milling, the synergistic effect of rare earth elements and nitrogen elements is used to solve the problem of excessive additives and poor low temperature kinetics in the aluminum hydride composite hydrogen storage system, and efficient hydrogen storage and release are achieved.

CN119551631AActive Publication Date: 2025-03-04CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES

Patent Information

Application Number
CN202510113365.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-03-04
Estimated Expiration
2045-01-24

AI Technical Summary

Technical Problem

The amount of additives used in the existing aluminum hydride composite hydrogen storage system is too large and the low temperature kinetics are poor, making it difficult to meet the actual needs of portable hydrogen fuel cells.

Method used

The composite hydrogen storage material was prepared by mixing aluminum hydride powder with lanthanum nitride particles and undergoing multiple ball milling treatments under an argon atmosphere. This method uses the synergistic effect of rare earth elements and nitrogen elements to reduce the dehydrogenation temperature of aluminum hydride and improve the dehydrogenation kinetics in the low-temperature zone.

Benefits of technology

It is achieved to improve the hydrogen storage capacity and dehydrogenation efficiency of aluminum hydride materials at lower temperatures, reduce the amount of additives, and shorten the ball milling treatment time and reduce capacity loss.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119551631A_ABST
    Figure CN119551631A_ABST
Patent Text Reader

Abstract

The invention discloses a composite hydrogen storage material as well as a preparation method and application thereof, and belongs to the technical field of hydrogen storage materials and preparation thereof. The problems that an existing aluminum hydride composite hydrogen storage system is too much in additive dosage, poor in low-temperature kinetics and the like are solved. According to the invention, the rare earth nitride is used as an additive, the multivalent characteristic of the rare earth element is used as an active center, and the nitrogen element has an attraction effect on negative hydrogen, so that the dissociation and transmission of hydrogen are accelerated; the rare earth element can perform electron transmission with aluminum hydride by taking a nitrogen active site as a bridge, so that a synergistic effect between the rare earth element and the aluminum hydride is realized, the affinity of the rare earth element and a hydrogen element is enhanced through an electron donating effect of the nitrogen element, the dehydrogenation temperature of the aluminum hydride material is reduced, and meanwhile, the dehydrogenation kinetics of a low-temperature region of the aluminum hydride material is also improved. In addition, the preparation process of the composite hydrogen storage material is simple and mature, raw materials are cheap and easy to obtain, and large-scale industrial production is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a composite hydrogen storage material and a preparation method and application thereof, belonging to the technical field of hydrogen storage materials and preparation thereof. Background Art

[0002] Solid light metal hydrides combine high hydrogen storage density, mild dehydrogenation conditions and high safety. The dehydrogenated hydrogen has high purity and can be directly used as a direct hydrogen source for portable hydrogen fuel cells. It is one of the most promising hydrogen storage materials currently.

[0003] For example, aluminum hydride (AlH3) has an ultra-high hydrogen storage capacity (~10.1wt%) and a moderate dehydrogenation temperature (~140°C), making it very suitable as a material for portable hydrogen storage tanks. However, considering the unnecessary weight caused by the operating temperature range of the fuel cell and the heat exchange system, the aluminum hydride hydrogen storage system needs to further reduce its dehydrogenation temperature and improve its dehydrogenation kinetics in the low temperature zone. Therefore, optimizing light metal hydrides and constructing new composite hydrogen storage materials that better meet actual needs is a difficult problem that needs to be overcome in the current technical field.

[0004] In the prior art, relevant research on optimizing aluminum hydride by using rare earth oxide additives has made certain progress, but the capacity of the composite product is generally lower than 9wt%. Summary of the invention

[0005] In order to solve the problems of excessive additive dosage and poor low-temperature kinetics in the existing aluminum hydride composite hydrogen storage system, the present invention provides a composite hydrogen storage material and a preparation method and application thereof.

[0006] The technical solution of the present invention: One of the purposes of the present invention is to provide a composite hydrogen storage material, which is composed of aluminum hydride powder and lanthanum nitride particles.

[0007] It is further defined that the mass proportion of lanthanum nitride particles in the composite hydrogen storage material is 1-10%.

[0008] It is further specified that the mass proportion of lanthanum nitride particles in the composite hydrogen storage material is 5%.

[0009] The second object of the present invention is to provide a method for preparing the above-mentioned composite hydrogen storage material, specifically, mixing aluminum hydride powder and lanthanum nitride particles, and performing ball milling treatment multiple times under a protective atmosphere to obtain the composite hydrogen storage material.

[0010] It is further defined that the particle size of lanthanum nitride is 1-10 μm.

[0011] It is further defined that the rotation speed of the ball milling process is 350 rpm.

[0012] It is further defined that the ball-to-material ratio of the ball milling process is 50:1.

[0013] It is further defined that the number of ball milling treatments is 4 times.

[0014] It is further limited that the single ball milling time is 15 minutes, and after the single ball milling is completed, it is stopped for 10 minutes, and the rotation direction of the ball milling disk is changed before the next ball milling treatment.

[0015] It is further defined that the protective atmosphere is argon.

[0016] Beneficial effects of the present invention: (1) The present invention uses rare earth nitride as an additive, utilizes the multivalent state characteristics of rare earth elements as active centers, and utilizes the certain attraction of nitrogen to negatively charged hydrogen to accelerate the dissociation and transmission of hydrogen. At the same time, since nitrogen has a rich valence state, rare earth elements can use nitrogen active sites as a bridge to transmit electrons with aluminum hydride, thereby achieving a synergistic effect between the two. The electron donating effect of nitrogen enhances the affinity between rare earth elements and hydrogen, reduces the dehydrogenation temperature of aluminum hydride materials, and also improves the dehydrogenation kinetics of aluminum hydride materials in the low temperature zone.

[0017] (2) The present invention utilizes the synergistic effect of nitrogen and rare earth elements to reduce the amount of additives used, thereby increasing the capacity of the composite hydrogen storage material. The test results show that when the addition amount of lanthanum nitride is 5wt%, the initial dehydrogenation temperature of the composite material is reduced to 80°C, the capacity reaches 9.2wt%, and the effective hydrogen storage capacity at 100°C and 2h exceeds 7.0wt%.

[0018] (3) The present invention utilizes the synergistic effect of nitrogen and rare earth elements to obtain excellent catalytic activity. Therefore, the ball milling treatment time only needs 1 hour, which reduces the initial hydrogen release temperature of the aluminum hydride hydrogen storage material from 145°C to below 85°C. The capacity loss during the ball milling process is only 0.37wt%, and the capacity retention rate is 96%.

[0019] (4) The preparation process of the composite hydrogen storage material provided by the present invention is simple, mature and stable, and the raw materials are cheap and easily available, which is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a comparison diagram of the temperature-controlled dehydrogenation curves of the composite hydrogen storage material prepared in Examples 1-2 and Comparative Example 1 and the original aluminum hydride; Figure 2 It is a differential curve comparison diagram of the temperature-controlled dehydrogenation curve of the composite hydrogen storage material prepared in Examples 1-2 and Comparative Example 1 and the original aluminum hydride; Figure 3 It is a comparison diagram of the 100°C constant temperature dehydrogenation curves of the composite hydrogen storage material prepared in Examples 1-2 and Comparative Example 1 and the original aluminum hydride; Figure 4 This is the N 1s orbital XPS spectrum of the composite hydrogen storage material prepared in Example 2 before dehydrogenation; Figure 5 This is the N 1s orbital XPS spectrum of the composite hydrogen storage material prepared in Example 2 after dehydrogenation. DETAILED DESCRIPTION

[0021] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0022] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.

[0023] Example 1 Weigh 0.570g of aluminum hydride powder and 0.030g of commercially available lanthanum nitride particle sample (particle size of 1~10μm) respectively, mix them evenly in an argon atmosphere, and the total mass is 0.6g. Then put the mixed sample into a ball mill, and add stainless steel balls (total mass 30g) into the ball mill at a ratio of 50:1. The ball mill is sealed in an argon atmosphere, and the sealed ball mill is placed in a planetary ball mill for mechanical ball milling. The ball mill speed is 350rpm, and the ball milling time is 1h. In order to prevent the temperature of the tank from being too high and causing the aluminum hydride to decompose due to heat, the ball milling time is divided into 4 sections, each section is 15min, and the rotation direction of the planetary ball mill is changed between each two sections. After the ball milling process is completed, the ball mill is taken out and opened in an argon atmosphere to collect the lanthanum nitride-aluminum hydride composite hydrogen storage material product, named LaN-0.05.

[0024] Example 2 Weigh 0.552g aluminum hydride powder and 0.048g lanthanum nitride sample (particle size 1~10μm) respectively, mix them evenly in an argon atmosphere, and the total mass is 0.6g. Then put the mixed sample into a ball mill, and add stainless steel balls (total mass 30g) into the ball mill at a ratio of 50:1. Seal the ball mill in an argon atmosphere, and place the sealed ball mill in a planetary ball mill for mechanical ball milling. The ball mill speed is 350rpm, and the ball milling time is 1h. In order to prevent the aluminum hydride from being decomposed by heat due to excessive tank temperature, the ball milling time is divided into 4 sections, each section is 15min, and the rotation direction of the planetary ball mill is changed between each two sections. After the ball milling process is completed, take out the ball mill and open the can in an argon atmosphere to collect the lanthanum nitride-aluminum hydride composite hydrogen storage material product, named LaN-0.08.

[0025] Comparative Example 1 Weigh 0.6g of aluminum hydride powder into a ball mill, and add stainless steel balls (total mass 30g) to the ball mill at a ratio of 50:1. Seal the ball mill in an argon atmosphere and place the sealed ball mill in a planetary ball mill for mechanical ball milling. The ball mill speed is 350rpm and the ball milling time is 1h. In order to prevent the aluminum hydride from being decomposed by heat due to excessive tank temperature, the ball milling time is divided into 4 sections, each section is 15min, and the rotation direction of the planetary ball mill is changed for 10min between each section. After the ball milling process is completed, take out the ball mill and open the can in an argon atmosphere to collect the nano-aluminum hydride powder, named BM AlH3.

[0026] Effect example (1) The composite hydrogen storage materials and aluminum hydride powder prepared in Examples 1-2 and Comparative Example 1 were subjected to temperature-controlled dehydrogenation tests and constant-temperature dehydrogenation tests at 100°C, and the corresponding dehydrogenation amounts were calibrated. The specific temperature-controlled dehydrogenation test was a constant-rate heating test with a heating rate of 2°C / min. The calibrated initial dehydrogenation temperature was the zero-point temperature when y was always greater than 0 in the differential curve of the temperature-controlled dehydrogenation curve (affected by the test conditions, this temperature is used as a reference and comparison, and does not mean that the hydrogen storage material does not undergo dehydrogenation reaction at all at this temperature). In addition, considering the actual working time of the portable tank, the dehydrogenation capacity within 2 hours was selected as the effective capacity of constant-temperature dehydrogenation at 100°C.

[0027] Test results such as Figure 1-3As shown, comprehensive analysis shows that the initial dehydrogenation temperature of aluminum hydride powder is 145°C, the total dehydrogenation amount is 10.0wt%, the effective dehydrogenation amount is 0.08wt% at 100°C for 2h, and no dehydrogenation at 80°C. The initial dehydrogenation temperature of BM AlH3 prepared in Comparative Example 1 is 109°C, the total dehydrogenation amount is 9.93wt%, and the effective dehydrogenation amount is 3wt% at 100°C for 2h. The initial dehydrogenation temperature of the LaN-0.05 composite hydrogen storage material prepared in Example 1 is 78°C, which is about 67°C lower than that of aluminum hydride powder, and the total dehydrogenation amount can reach 9.24wt%, and the effective dehydrogenation amount at 100°C for 2h reaches 7.08wt%. The initial dehydrogenation temperature of the LaN-0.08 composite hydrogen storage material prepared in Example 2 is 82°C, the total dehydrogenation amount can reach 9.03wt%, and the effective dehydrogenation amount at 100°C for 2h is 6.86wt%.

[0028] (2) The composite hydrogen storage material prepared in Example 2 was further subjected to X-ray photoelectron spectroscopy analysis before and after dehydrogenation. The test results are as follows: Figure 4 and 5 As shown. From the XPS analysis of the electronic state of the element surface, it can be seen that nitrogen is involved in the electron transfer process. This process is divided into two parts. The first is that the electron-withdrawing effect between nitrogen and negatively charged hydrogen increases the electron concentration of hydrogen and enhances its reducibility, which weakens the Al-H bond. This effect is synergistic with the "hydrogen pump" effect of rare earth elements, which can promote the dissociation and transfer of hydrogen at the same time, effectively improving the activity of the catalyst. The second is that it acts as a bridge for electron transfer, connecting the electron exchange process between rare earth elements and metal centers, and improving the electron exchange efficiency. In summary, due to its weak electronegativity, nitrogen has a weak ability to bind electrons and high electronic activity, so it can play a more obvious role in improving catalytic activity. In summary, the composite hydrogen storage material provided by the present invention utilizes the synergistic effect of rare earth elements and nitrogen elements, ensures the high capacity characteristics of aluminum hydride, and at the same time reduces the dehydrogenation temperature of the aluminum hydride material and improves the dehydrogenation reaction kinetics of the aluminum hydride material, thereby realizing low-temperature rapid dehydrogenation of the aluminum hydride material.

[0029] The above description is only a preferred embodiment of the present invention. In view of the fact that technicians in the field of the present invention can make appropriate changes and modifications to the above implementation, the present invention is not limited to the specific implementation described above. Some modifications and changes to the present invention should also fall within the scope of protection of the claims of the present invention.

Claims

1. A composite hydrogen storage material, characterized in that: It is a composite of aluminum hydride powder and lanthanum nitride particles.

2. The composite hydrogen storage material according to claim 1, characterized in that: The mass proportion of lanthanum nitride particles in the composite hydrogen storage material is 1~10%.

3. The composite hydrogen storage material according to claim 2, characterized in that: The mass proportion of lanthanum nitride particles in the composite hydrogen storage material is 5%.

4. A method for preparing the composite hydrogen storage material according to any one of claims 1 to 3, characterized in that: Aluminum hydride powder and lanthanum nitride particles are mixed and subjected to multiple ball milling treatments under a protective atmosphere to obtain a composite hydrogen storage material.

5. The preparation method according to claim 4, characterized in that: The particle size of lanthanum nitride is 1~10μm.

6. The preparation method according to claim 4, characterized in that: The rotation speed of the ball milling process was 350 rpm.

7. The preparation method according to claim 4, characterized in that: The ball-to-material ratio of ball milling is 50:

1.

8. The preparation method according to claim 4, characterized in that: The ball milling process was performed 4 times.

9. The preparation method according to claim 4 or 8, characterized in that: The single ball milling time is 15 minutes, and after the single ball milling is completed, it is stopped for 10 minutes, and the rotation direction of the ball mill is changed before the next ball milling treatment.

10. The preparation method according to claim 4, characterized in that: The protective atmosphere was argon.

Citation Information

Patent Citations

  • Preparation method of composite hydride hydrogen storage material and composite hydride hydrogen storage material

    CN107915203A

  • Rare earth oxide doped aluminum hydride hydrogen-storage material and preparation method thereof

    CN110371925A

  • Polymer-doped aluminum hydride hydrogen storage material and preparation method thereof

    CN116101974A

  • Modified catalyst and application thereof in modification of aluminum hydride hydrogen storage system

    CN117504918A

  • Reversible hydrogen storage composition

    US20010018939A1

Cited By

  • Composite hydrogen storage material and preparation method thereof

    CN120097278A